A Comprehensive View on the Human Antibody Repertoire Against Staphylococcus aureus Antigens in the General Population - Meyer, Tanja C.; Michalik, Stephan; Holtfreter, Silva; Weiss, Stefan; Friedrich, Nele; Völzke, Henry; Kocher, Thomas; Kohler, Christian; Schmidt, Frank; Bröker, Barbara M.; Völker, Uwe (Frontiers in Immunology, 2021)
Our goal was to provide a comprehensive overview of the antibody response to Staphylococcus aureus antigens in the general population as a basis for defining disease-specific profiles and diagnostic signatures. We tested the specific IgG and IgA responses to 79 staphylococcal antigens in 996 individuals from the population-based Study of Health in Pomerania. Using a dilution-based multiplex suspension array, we extended the dynamic range of specific antibody detection to seven orders of magnitude, allowing the precise quantification of high and low abundant antibody specificities in the same sample. The observed IgG and IgA antibody responses were highly heterogeneous with differences between individuals as well as between bacterial antigens that spanned several orders of magnitude. Some antigens elicited significantly more IgG than IgA and vice versa. We confirmed a strong influence of colonization on the antibody response and quantified the influence of sex, smoking, age, body mass index, and serum glucose on anti-staphylococcal IgG and IgA. However, all host parameters tested explain only a small part of the extensive variability in individual response to the different antigens of S. aureus.